Comparison of Three Measurement Principles on Water Triple Oxygen Isotopologues - Ranjan, Shyam; Leuenberger, Markus C. (Frontiers in Earth Science, 2021)
The widespread method for measuring 17O (17O excess) is an offline CoF3 (Cobalt tri-fluoride) conversion of water to molecular oxygen with subsequent isotope determination by dual inlet mass spectrometry. High precisions for 17O measurements, using CoF3 water conversion, are so far only possible with off-line methods. Here we report on an improved and modified online continuous flow method intended for high precision triple oxygen isotope analysis. This method is improved by optimizing the reactor (site for conversion of H2O into oxygen through the chemical reaction) compositions, size of the fused silica capillary, flow regulator and data treatment. Our modified online continuous method was further compared with the recently developed cavity ring down measurement principle. The precision is significantly better for the commercially available laser-based system than our current version of improved online CoF3 conversion method using mass spectrometry. Factors, identified for limiting precision in our continuous flow system are: (i) compaction of the reactor with time that leads to the restriction of flow rate of carrier gas, (ii) the CoF3 treatment, (iii) the amount of CoF3 inside the reactor, (iv) the pore size of the steel frit, and (v) the metallic tube. Changes in all of these items as well as the dimension of the fused silica capillary, the positioning of the fused silica capillary in the open split, and the memory effect can also lead to a declining precision. These limiting factors for precision still provide us enough space for further improvement of our improved online method which will be worthwhile for measurement of smaller aliquot samples as fluid inclusions for palaeoclimatic applications. With present improvement, multiple injections (n=15 or even more) should be applied to obtain a precision better than 10 permeg for D17O. Furthermore, a comparison of the laser-based system with an improved conventional equilibration method has been made on precipitation samples originating from Jungfraujoch.